Production function as a measure of school education quality - Ejsmont, Wiktor (Funkcja produkcji jako miernik jakości kształcenia szkoły, 2009)
This paper presents a model for measuring school (university) education quality on the basis of individual teacher (lecturer) quality, similarly to the model postulated by Bishop and Wößmann. Quality tuition shapes the recognition of the institution (school or university). The postulated model describes the behaviour of a given education institution as a whole. The quality of education in a given institution is represented as a process affected by all teachers involved. The paper also presents mathematical substantiation for the local maximum of the utility function resulting from the educational quality of the institution
Didactics of Mathematics, 2009, Nr 5-6 (9-10), s. 79-88
Keywords: human capital; production functions; education quality